Montmorillonite Clay 2021
DOI: 10.5772/intechopen.96524
|View full text |Cite
|
Sign up to set email alerts
|

Study of Adsorption Properties of Bentonite Clay

Abstract: The clay used in this study was the bentonite from Mostagnem, Algeria. This material is used in many fields such as drilling, foundry, painting, ceramics, etc. It can also be applied in the treatment of wastewaters from chemical industries by means of adsorption. In this chapter the physicochemical properties of bentonite were determined by using several analyses techniques such as chemical composition, XRD, FTIR and SBET. The bentonite was intercalated by aluminum poly-cations solution and cethytrimethyl ammo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…These grains form a stack of sheets, indicating clay layers. A little bright crystallite settles on the sample's surface, which could be made of free silica [37]. In contrast, the SEM micrograph, Fig.…”
Section: Sem Analysismentioning
confidence: 93%
See 1 more Smart Citation
“…These grains form a stack of sheets, indicating clay layers. A little bright crystallite settles on the sample's surface, which could be made of free silica [37]. In contrast, the SEM micrograph, Fig.…”
Section: Sem Analysismentioning
confidence: 93%
“…It was found that bond O-H deformation of the contained water molecules is related to the small band at 1640 cm −1 . The band at 3628 cm −1 can also be related to OH-stretching bands [37].…”
Section: Ftir Analysismentioning
confidence: 99%
“…Moreover, the BET specific surface area of inorganic bentonite is 59 m 2 /g, whereas of the organo-modified montmorillonite it is 194 m 2 /g [ 43 ]. The higher surface area of organically modified montmorillonite compared to bentonite is an indicative factor for the lower adsorption of bioactive compounds onto the inorganic bentonite in comparison to the organo-modified montmorillonite.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical and mechanical stabilities, layered structure, tendency to hold water in the interlayer sites, and high specific surface area and cation exchange capacity (CEC) have made clay minerals excellent adsorbent materials [ 14 ]. Among clay minerals, bentonite, which is very soft plastic clay and is a 2:1 clay mineral type composed primarily of montmorillonite, is commonly used in many fields, including painting, foundry, and ceramics [ 14 ]. It can also be applied in wastewater treatment by means of adsorption.…”
Section: Introductionmentioning
confidence: 99%